Engineering Mathematics I : A Case Study of First Year Students at Faculty of Engineering, UNIMAS - Kuryati, Kipli; Norazlina, Bateni; Mohd. Shahril, Osman; Norsuzailina, Mohamed Sutan; Annie, Joseph; Onni Suhaiza, Selaman (Elsevier Ltd., 2012)
The subject of mathematics is important as a prerequisite and requirement as most topics in engineering courses widely employ these fundamentals. The paper will describe an analysis based on Engineering Mathematics I course results for first year student of Semester I 2009/2010 academic year at the Faculty of Engineering, University of Malaysia Sarawak (UNIMAS). The aim is to identify the topics within Engineering Mathematics I, which may cause some difficulties for new students to understand. The performance that directly related to the students’ weaknesses is obtained from the continuous assessments of the course, end of semester report analysis based on course outcomes and item analysis. The results will be used as the basis for improving the teaching and learning process for this course.